Odpowiedzi

2009-11-19T20:32:30+01:00
A) (x+1) (x-2)+(x+2)(x-1)= x²-2x+x-2+x²-x+2x-2 = 2x²-4
b)(5k+m)(k-2n)-k(4k+n)=5k²-10kn+mk-2mn-4k²-kn=k²-11kn+mk-2mn

;)
2009-11-19T20:35:01+01:00
A) x² - 2 + x² + 2 = 2x²
b) 5k² - 2mn - 4k² + kn = k² - 2mn + kn
Najlepsza Odpowiedź!
2009-11-19T20:35:44+01:00
A) (x+1) (x-2)+(x+2)(x-1)=z x(do potęgi drugiej)-2x+x-2+x(do potegi drugiej)-x+2x-2-2x(do potegi drugiej)-2 (nie piszesz -2x+2x -x+x bo to jest wynik 0 ktorego sie ne pisze tylko przekreslasz!)
b) (5k+m)(k-2n)-k(4k+n)= 5k-10kn+km-2mn-4k-2=k-11kn+km-2mn
1 5 1